Physical Discomfort Experienced in Traditional Education and Tablet-Assisted Education: A Comparative Literature Analysis - Uyal, Banu Numan; Yel, Elif Binboga; Korhan, Orhan (Springer International Publishing Ag, 2018)
With advances in technology, various forms of computers have become more involved in education. In particular, tablet computers are actively used for educational purposes nowadays. Given the fact that musculoskeletal, postural, and ocular developments of children and adolescents are still not complete, potential physical issues resulting from usage of new technologies must not be disregarded. Physical problems or challenges experienced by children and adolescent students will be involved in this research from the perspectives of traditional education and tablet-assisted education. In a sense, a comparative review of the available literature is used in the study to analyze and identify the commonalities and differences in physical problems experienced by students.
Global Joint Conference on Industrial Engineering and Its Application Areas (GJCIE ) -- JUL 20-21, 2017 -- Vienna, AUSTRIA
Keywords: Students; Physical challenges; Traditional education; Tablet-assisted education